Statistics and TQM in industrial continuing education. (4th August 2014) - Bergman, Bo; Klefsjo, Bengt
The urgent industrial transformation towards Total Quality Management and the role of statistics in this transformation are discussed. Implications for the teaching of statistics and TQM principles are drawn. In particular, implications for continuing education are discussed.